Do estimates of blood loss differ between student midwives and midwives? A multicenter cross-sectional study. (April 2018) - Pranal, Marine; Guttmann, Aline; Ouchchane, Lemlih; Parayre, Ines; Rivière, Olivier; Leroux, Sylvie; Bonnefont, Sylvie; Debost-Legrand, Anne; Vendittelli, Françoise
Abstract: Objective: the principal objective of this study was to assess the quality of blood loss estimates by midwives and student midwives. The secondary objectives were: to assess the intraobserver agreement of visual blood estimates and the rate of underestimation of blood loss by participants, and to estimate the sensitivity, specificity, and negative likelihood ratio of these estimates for clinically pertinent blood losses (≥ 500 mL and ≥ 1000 mL). Design: multicenter cross-sectional study. Setting: thirty-three French maternity units and 35 French midwifery schools participated in this study. Participants: volunteer French midwifery students ( n = 463) and practicing midwives ( n = 578). Intervention: an online survey showed 16 randomly ordered photographs of 8 different simulated blood quantities (100, 150, 200, 300, 500, 850, 1000, and 1500 mL) with a reference 50-mL image in each photo and asked participants to estimate the blood loss. The visual blood loss estimates were compared with Fisher's exact test. Intraobserver agreement for these estimates was assessed with a weighted kappa coefficient, and the negative predictive values (probability of no hemorrhage when visual estimate was negative) were calculated from prevalence rates in the literature. Findings: of the 16, 656 estimates obtained, 34.1% were accurate, 37.2% underestimated the quantity presented, and 28.7% overestimated it. Analyses of the intraobserver reproducibility between the two estimates of the same photograph showed that agreement was highest (weighted kappa ≥ 0.8) for the highest values (1000 mL, 1500 mL). For each volume considered, students underestimated blood loss more frequently than midwives. In both groups, the negative predictive values regarding postpartum hemorrhage (PPH) diagnosis (severe or not) were greater than 98%. Key conclusions and implications for practice: student midwives tended to underestimate the quantity of blood loss more frequently than the midwives. Postpartum hemorrhage (≥ 500 mL) was always identified, but severe postpartum hemorrhage (≥ 1000 mL) was identified in fewer than half the cases. These results should be taken into account in training both student midwives and practicing professionals. Highlights: Visual estimates are widely used throughout the world as the first-line method for diagnosing immediate PPH. We observed that the global percentage of accurate estimates was low (34.1%). Student midwives tended to underestimate the quantity of blood loss more frequently than the midwives. PPH (≥ 500 mL) was always identified, but severe PPH (≥ 1000 mL) was identified in less than half the cases.